Імітаційні моделі з інтерфейсом віртуальної реальності при розробці тренажерів лікаря ЛДК - Тимашов, Є.О. (Комп’ютерні засоби, мережі та системи, 2014)
Analysis of the requirements for the trainer for the doctor mobile medical devices and information technology is considered to create an interface of virtual reality systems LDK.